Maternal Knowledge Factor, Maternal Age and Maternal Parity Associated with Genesis of Normal Delivery at Palembang Hospital of Bari Year 2017: Faktor Pengetahuan Ibu, Umur Ibu dan Paritas Ibu yang Berhubungan dengan Kejadian Persalinan Normal di RSUD Palembang Bari Tahun 2017 - Wahyuningsih, Juliana Widyastuti (Sriwijaya Journal of Medicine, 2018)
Childbirthis a processLabor of opening and depleting the cervix and the fetus down into the birth canal. Birth is a process in which the fetus and amniotic are pushed out through the birth canal. (Sarwono, 2008). According to the World Health Organization (WHO) estimates more than 585,000 mothers annually die during pregnancy or childbirth. Indonesia Health Demographic Survey (SDKI) Survey in 2012, Maternal Mortality Rate in Indonesia is still high at 359 per 100,000 live births. The purpose of this study is the knowledge of maternal knowledge, maternal age, and maternal parity associated with normal birth events at Palembang Bari Hospital 2017. This study used analytical survey method with cross sectional approach. The population in this study were all maternal mothers at the Palembang Bari Hospital in 2017. Sampling in the study was conducted non-randomly with the technique of "Accidental Sampling". Data analysis was done univariat and bivariate with Chi-Square statistical test with significance level Î± = 0,05. The result of this research shows that there is correlation between mother's knowledge with normal delivery incidence with p value 0,001, there is correlation between mother age with normal delivery incidence with p value 0,009, there is relation between mother parity with normal delivery incidence with p value 0,001. From result of this research hopes healthcare workers can improve normal delivery care services and more often to carry out maternal safety counseling.